Life Cycle Analysis for sugarcane production in six regions of Costa Rica - Montenegro Ballestero, Johnny (2022)
[Introduction]: Different agricultural practices implemented during sugarcane (Saccharum officinarum) production phase generate greenhouse gases (GHG), and there is great interest in quantifying and identifying their origin to determine the practices that emit the highest amounts. [Objectives]: To use the life cycle analysis to identify the main sources of GHG emissions in the sugarcane production process, to generate base information to develop mitigation alternatives and, to know the crop emission efficiency. [Methodology]: All field work and transport of stems to the mill were considered. The use of machinery and agrochemicals, fertilizers, as well as the transportation of sugarcane to the mill was determined. The emissions of methane and nitrous oxide were calculated by using national emission factors and those suggested by the IPCC. Each gas was converted to CO2eq, the way the results are reported. [Results]: The largest source of emission (73.6 %) was nitrogen fertilization, followed by burning carried out prior to harvest (13.2 %). Emission efficiency varies with the producing region, being the national average of 26.9  kg CO2eq t-1 of cane and 247.5 kg CO2eq t-1 of sugar. Some mitigation options are presented and discussed. [Conclusions]: It is shown that Costa Rican sugarcane activity has a better efficiency than other sugarcane producing countries, and that if mitigation options are implemented, GHG emissions could be reduced, and this could contribute to differentiate the national production in the markets.